2014
DOI: 10.1111/wrr.12152
|View full text |Cite
|
Sign up to set email alerts
|

Application of stems cells in wound healing—An update

Abstract: Wound healing is a complex but well-orchestrated tissue repair process composed of a series of molecular and cellular events conducted by various types of cells and extracellular matrix. Despite a variety of therapeutic strategies proposed to accelerate the healing of acute and/or chronic wounds over the past few decades, effective treatment of chronic nonhealing wounds still remains a challenge. Due to the recent advances in stem cell research, a dramatic enthusiasm has been drawn to the application of stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 105 publications
0
41
0
1
Order By: Relevance
“…They included both preclinic trials with animal models, such as mouse, rat, dog, or pig, as well as clinic ones with humans (Nuschke, 2014;Li et al, 2015b;Maranda et al, 2016). Both autologous and allogenous MSC from different origins have been used, including bone marrow, adipose tissue, umbilical cord, and the stromal vascular fraction, among others (Teng et al, 2014). Interestingly, several works have demonstrated that conditioned media from MSC cultures have a similar-or even higher-regenerative capacity than such cells, when applied to wounds.…”
Section: Skin Wound Healingmentioning
confidence: 99%
“…They included both preclinic trials with animal models, such as mouse, rat, dog, or pig, as well as clinic ones with humans (Nuschke, 2014;Li et al, 2015b;Maranda et al, 2016). Both autologous and allogenous MSC from different origins have been used, including bone marrow, adipose tissue, umbilical cord, and the stromal vascular fraction, among others (Teng et al, 2014). Interestingly, several works have demonstrated that conditioned media from MSC cultures have a similar-or even higher-regenerative capacity than such cells, when applied to wounds.…”
Section: Skin Wound Healingmentioning
confidence: 99%
“…Despite their great differentiation potential, application of ESCs at clinical level is still facing a number of problems, including ethical concerns and legislative debates (Rosner et al 2014;Teng et al 2014). Furthermore, using ESCs in therapeutic procedures may result to tumorigenesis (Dressel et al 2008;BenDavid and Benvenisty 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ASCs have been tested in multiple preclinical trials on wound healing and have been found to significantly enhance cutaneous wound healing and increase blood vessel formation [14,32]. A 2007 study showed that treating the radiated skin of cancer patients with purified autologous lipoaspirate led to improvements on a clinical and histological level [33].…”
Section: Stem Cell Populations For Cutaneous Repairmentioning
confidence: 99%